Imobilisasi Tembaga (Cu) dan Netralisasi Aktivitas Ion Hidrogen (pH) pada Limbah Cair Industri Peleburan Emas Dengan Batu Gamping (Limestone) - Setiani, Onny; Raharjo, Mursid; Hanani, Yusniar; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2002)
The objectives of this research were to determine the effectiveness of  limestones in neutralizing hydrogen ion activity (pH), immobilizing cooper (Cu) and to implement a waste water treatment process from the gold molten industry using a cost-effective method to prevent the environment contamination from hazardous wastes. Before  implementing technology, a preliminary study was done to determine a simple and cost effective  method to neutralize pH, immobilize and sedimentation of Copper (Cu)  using limestones (CaCO3). The results of laboratory examination in preliminary study  showed that limestones may decrease the concentration of Cu from 23,070 mg/L to 0.711 mg/L, TDS from 30,302 mgLl to 18,289 mg/L and neutralize pH from 1.0-3.0 to 7.0. This research demonstrate that limestones may provide a cost effective method to immobilize  Cu and neutralize contaminated wastewater of the gold molten industry. Since the technology  is very simple, it is  suggested  to be used by home scale or  small industry to protect the environment from toxic waste pollution.   Keywords: Immobilizing cooper, lime stone, neutralization, waste water.